Features of interethnic trust of various ethnic groups representatives of a multicultural region - Alena V. Alborova; Svetlana V. Dreeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents the results of a study conducted in 2021 of perceptions of trust in interethnic relations of representatives of various ethnic groups of a multicultural region. The purpose of the study was to examine the components of trust of ethnophores, to identify ideas about the factors affecting interethnic trust. The study used the authors methodology to assess the structure of ideas about interethnic trust, trust factors, as well as revealing the self-assessment of the ability to trust in interethnic relations. Respondents were offered a modification of the methodology Unfinished Sentences by Sachs Levy in the authors modification, reflecting the respondents understanding of the interethnic aspect of trust and the degree of trusting relationships to individual ethnic groups. When analyzing the features of the ideas of interethnic trust, the methodological development of the assessment of the structure of the ideas of trust was used by M.M. Borisova, S.D. Gurieva. The Students t-test was used in the study to determine the statistical significance of differences in average values. The sample consisted of 418 respondents, representatives of ethnic groups of Ossetians, Russians, Chechens, Kabardians, Georgians who live in the territory of the North Caucasus Federal District of the Russian Federation (Republic of North Ossetia-Alania, Chechen Republic and Kabardino-Balkarian Republic). The study involved two age groups: the first respondents from 16 to 25 years old; the second respondents over 25 years old. The results of our study showed that the cognitive component in the structure of perceptions of trust prevails throughout the sample of subjects, regardless of age and ethnicity. As factors influencing interethnic trust, respondents identified: personal qualities of ethnophores, behavioral characteristics, the history of relations between peoples, social environment, knowledge about other peoples, the state, as well as the media.